Choice in a self?control paradigm: quantification of experience?based differences (1984)
Previous quantitative models of choice in a self?control paradigm (choice between a larger, more?delayed reinforcer and a smaller, less?delayed reinforcer) have not described individual differences. Two experiments are reported that provide additional quantitative data on experience?based differences in choice between reinforcers of varying sizes and delays. In Experiment 1, seven pigeons in a self?control paradigm were exposed to a fading procedure that increased choices of the larger, more?delayed reinforcer through gradually decreasing the delay to the smaller of two equally delayed reinforcers. Three control subjects, exposed to each of the small?reinforcer delays to which the experimental subjects were exposed, but for fewer sessions, demonstrated that lengthy exposure to each of the conditions in the fading procedure may be necessary in order for the increase to occur. In Experiment 2, pigeons with and without fading?procedure exposure chose between reinforcers of varying sizes and delays scheduled according to a concurrent variable?interval variable?interval schedule. In both experiments, pigeons with fading?procedure exposure were more sensitive to variations in reinforcer size than reinforcer delay when compared with pigeons without this exposure. The data were described by the generalized matching law when the relative size of its exponents, representing subjects' relative sensitivity to reinforcer size and delay, were grouped according to subjects' experience.